Needs Assessment of Electronic Portfolio Development for Nurse Anesthetist Students - Apidechakul, Parichad; Phanthananphokhin, Napichayakarn; Ruttananukool, Nichaon; Vichitvejpaisal, Phongthara (Journal of The Royal Thai Army Nurses, 2025)
The transition and implementation of electronic portfolios for nurse anesthetist students requires a systematic needs assessment. This research aims to (1) compare the current status and needs for a portfolio, (2) prioritize requirements for development, and (3) gather opinions from anesthesia educators. A mixed-methods research design was used to survey the needs of 45 anesthesia nursing students and three nursing instructors to assess the current and desired state of the portfolio. Statistical analyses were performed using paired-sample t-tests and the Priority Needs Index (PNI). Significant differences were found between the students’ current and desired views in three dimensions of the portfolio: portfolio components: M = 3.56, SD = 0.73 (current) vs. M = 4.12, SD = 0.90 (desired); t(44) = 4.88, p < .001; portfolio technology: M = 3.25, SD = 1.09 (current) vs. M = 4.35, SD = 0.75 (desired); t(44) = 5.91, p < .001 Portfolio usefulness: M = 3.71, SD = 0.77 (current) vs. M = 4.18, SD = 0.80 (desired); t(44) = 5.09, p < 0.001 Students identified the most critical needs in technology (PNI mod = 0.34) and the less critical needs in obstacles (PNI mod = 0.12). The results underscore the importance of addressing gaps to develop user-friendly and effective systems.